A Study To Assess The Effectiveness Of Structured Teaching Programme On Knowledge Regarding Prevention Of Central Line Associated Bloodstream Infection Among Nursing Students At Selected College Of Nursing Kanpur - Moiz, Jyoti; Karamchandani, Shashwat; Alka, Alka; Himanshi, Himanshi; Monika, Monika; Stuti, Stuti; Vivek, Vivek (Journal of Neonatal Surgery, 2025)
A Central Line Associated Bloodstream Infection is a serious infection that occur when germ enter the bloodstream through the central line, health care providers must use stringent infection control practice each time they insert or check the line or change the dressing patient who get a Central Line Associated Bloodstream Infection have a fever and might also how red skin and soreness around the central line.(2) PROBLEM STATEMENT - A STUDY TO ASSESS THE EFFECTIVENESS OF STRUCTURED TEACHING PROGRAMME ON KNOWLEDGE REGARDING PREVENTION OF CENTRAL LINE ASSOCIATED BLOODSTREAM INFECTION AMONG NURSING STUDENTS AT SELECTED COLLEGE OF NURSING KANPUR. OBJECTIVE OF THE STUDY To assess the knowledge regarding prevention of Central Line Associated Bloodstream Infection among nursing students at selected college of nursing at Kanpur. To assess the effectiveness of structured teaching programme may improve the knowledge regarding prevention of Central Line Associated Blood Stream Infection. To determine the association between pre-test knowledge score regarding prevention of Central Line Associated Blood Stream Infection with their selected demographic variable. Methodology: Research Approach- Evaluative Quantitative Research Approach Research Design -quasiexperimental research design The result reveals that the mean value of knowledge score 537 in pre-test is 8.95 mean and SD is 2.09 and mean value of knowledge score1347 in post-test is 22.45 mean and SD is 1.24. The 't' test shows that the t = 46.14 and P(1.68) is <0.05 thus that the Planned teaching programme was effective' The knowledge score of pre-test mean8.95, mean percentage 35.85%, calculates t-value 46.144 The knowledge score of post-test mean, mean percentage 19.46%.